Philosophy Of Economics - EN36 - 202101 - Vega De La Cruz, Hugo Yamil (2021)
This course introduces you to key issues and ideas in the philosophy of science, with special focus on economics. The course is split into three modules: Models and Methods, Science and Society and The Political- Economy of Science